Innovation Strategy, Service Quality, Operational Performance, and Customer Loyalty in an Indonesian Freight Forwarder Company - Agus Pranoto; Lamsoudi Redouane (Journal of Managerial Sciences and Studies, 2026)
The rapid growth of Indonesia's freight forwarding industry has intensified pressure on companies to secure delivery orders and empty containers from shipping lines, particularly during peak-season periods when ship space is limited and customer demand fluctuates sharply. This study examines the direct and indirect effects of innovation strategy and service quality on customer loyalty through the mediating role of operational performance, using the case of an Indonesian freight forwarder company that has adopted a pre-booking system, an empty-container forecasting mechanism, and robotics-assisted shipment monitoring as its core innovation strategy. Data were collected from thirty respondents representing customer companies of the freight forwarder, using surveys, interviews, and focus group discussions, and analyzed through multiple linear regression and path analysis across two structural models, followed by hypothesis testing, an F-test, and Sobel bootstrapping procedures. The partial (t-test) results indicate that innovation strategy, service quality, and operational performance individually show no statistically significant effect on their respective dependent variables, whereas the simultaneous (F-test) results demonstrate that innovation strategy, service quality, and operational performance jointly exert a significant positive effect on customer loyalty, explaining 56.6 percent of its variance. These findings suggest that while none of the studied variables function as strong standalone predictors, their combined implementation—through disciplined pre-booking and forecasting practices, reliable shipment tracking technology, and consistent employee service quality—is essential for sustaining customer loyalty in the freight forwarding sector. The study offers managerial implications for logistics providers seeking to strengthen customer retention through integrated innovation and service-quality strategies, and it recommends that future research incorporate additional service-quality indicators such as assurance and empathy.